2020
DOI: 10.3390/nu12082394
|View full text |Cite
|
Sign up to set email alerts
|

Role of Vitamin C in Osteoporosis Development and Treatment—A Literature Review

Abstract: Osteoporosis and associated low energy fractures are a significant clinical problem, especially in the elderly population. The occurrence of a hip fracture is associated with significant mortality and a high risk of disability. For this, apart from the treatment of osteoporosis, effective prevention of both the development of the disease and related fractures is extremely important. One aspect of osteoporosis prevention is proper dietary calcium intake and normal vitamin D3 levels. However, there is some evide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
40
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 87 publications
(186 reference statements)
0
40
0
1
Order By: Relevance
“…Healthy, well-balanced nutrition can play an important role in the prevention and pathogenesis of osteoporosis, and in support of pharmacological therapy [6]. Several factors contribute to the development of osteoporosis in post-menopausal women, among which, low-grade inflammation, poor dietary habits, and sedentary and unhealthy lifestyles, such as smoking and alcohol consumption [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Healthy, well-balanced nutrition can play an important role in the prevention and pathogenesis of osteoporosis, and in support of pharmacological therapy [6]. Several factors contribute to the development of osteoporosis in post-menopausal women, among which, low-grade inflammation, poor dietary habits, and sedentary and unhealthy lifestyles, such as smoking and alcohol consumption [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Vitamin C deficiency is known to delay healing after bone fractures 16 and a higher dietary vitamin C intake is related to a reduction in femoral neck bone mineral density loss 17 . Consistently, several epidemiological 18 , 19 and review 20 studies have identified a positive association between bone mineral density and dietary vitamin C intake.…”
Section: Introductionmentioning
confidence: 53%
“…Vitamin C may not only exhibit antioxidant properties but may also exhibit prooxidant traits when consumed at higher concentrations, as the prior study found that 500 mg/day of vitamin C supplementation in men and women (aged between 17 and 49) for 6 weeks could promote oxidative DNA damage [ 49 ], and this may also be relevant to osteoporosis [ 45 ]. Furthermore, vitamin C at first was reported to act as an oxidant during osteoclastogenesis, and the oxidative stress accelerated osteoclast formation, but it caused osteoclast death at a later stage [ 50 , 51 ]. The main sources of vitamin C in the human diet are citrus fruits, pepper and kiwifruit, as well as cabbage, broccoli, kale or tomatoes [ 52 ].…”
Section: Bone and Osteoporosismentioning
confidence: 99%